Laboratory investigations into the origin of Mycoplasma synoviae isolated from a lesser flamingo (Phoeniconaias minor). Issue 1 (December 2016) - Catania, Salvatore; Gobbo, Federica; Ramirez, Ana; Guadagnini, Davide; Baldasso, Elisa; Moronato, Maria; Nicholas, Robin
Abstract Background The role of wild birds in the transmission and spread of mycoplasmas is not clear. Up to now differentMycoplasma species have been isolated from wild birds many of which are not considered pathogens sensu stricto for domestic flocks. This report describes the first isolation ofMycoplasma synoviae in a captive lesser flamingo (Phoeniconaias minor ) held in a zoo in Italy and the laboratory investigations performed to elucidate its origin. Results showed that the strain was similar to the MS-H vaccine strain using thevlh A methods although no vaccination with this product was used in the zoo. Case presentation This paper describes investigations into a case in which 10 of 12 adult lesser flamingos (Phoeniconaias minor ) died after having recently been moved from the Netherlands to a new zoo in Northern Italy. While most of the birds appeared to have died from the stress of movement and poor adaptation to their new environment, Mycoplasma synoviae, an important poultry pathogen in the layer and meat industry, was isolated for the first time from the trachea of one animal presenting catarrhal tracheitis and fibrinous airsacculitis. Genetic analysis of the conserved region of thevlhA was not able to differentiate the flamingo strain from the MS-H vaccine strain. However differences in the sequences of theobg gene of the flamingo and vaccine strain were detected. A test for temperature-sensitivity (ts ) gave ats − phenotype for the flamingo strain, in contrast to thets + status of the MS-H strain. Based on this information and knowing that the flamingos were not vaccinated againstM. synoviae, it is highly likely that the flamingo was infected with a genetically similar wild strain by contact with infected birds. Conclusions This case provides evidence for the potential role of international trade of ornamental birds as a possible route of introduction of new mycoplasma strains between countries, and moreover highlight thatvlh A gene sequencing was not sufficient to discriminate the wild strain isolated from the flamingo from the MS-H vaccine strain.